Reactive oxygen species-responsive polymer drug delivery systems - Liu, Jiaxue; Jia, Boyan; Li, Zhibo; Li, Wenliang (Frontiers in Bioengineering and Biotechnology, 2023)
Applying reactive polymer materials sensitive to biological stimuli has recently attracted extensive research interest. The special physiological effects of reactive oxygen species (ROS) on tumors or inflammation and the application of ROS-responsive polymers as drug-delivery systems in organisms have attracted much attention. ROS is a vital disease signal molecule, and the unique accumulation of ROS-responsive polymers in pathological sites may enable ROS-responsive polymers to deliver payload (such as drugs, ROS-responsive prodrugs, and gene therapy fragments) in a targeted fashion. In this paper, the research progress of ROS-responsive polymers and their application in recent years were summarized and analyzed. The research progress of ROS-responsive polymers was reviewed from the perspective of nanoparticle drug delivery systems, multi-responsive delivery systems, and ROS-responsive hydrogels. It is expected that our work will help understand the future development trends in this field.